The impact of a pharmacist-managed dosage form conversion service on ciprofloxacin usage at a major Canadian teaching hospital: a pre- and post-intervention study - Balen Robert M; Lau Tim TY; Ho Bradley P; Naumann Terryn L; Jewesson Peter J (BMC Health Services Research, 2005)
Abstract Background Despite cost containment efforts, parenteral (IV) ciprofloxacin appears to be overutilized at Vancouver General Hospital. In November 2003, the Pharmacist-managed intravenous to oral (IV-PO) Dosage Form Conversion Service was implemented, enabling autonomous pharmacist-initiated dosage form conversion for ciprofloxacin. This study evaluates characteristics of ciprofloxacin use prior to and following implementation of this conversion service. Methods This was a single-centre, two-phase (pre/post), unblinded study. Phase I occurred between November 12, 2002 and November 11, 2003 (365 days), and Phase II between November 12, 2003 and March 11, 2004 (120 days). All patients receiving ciprofloxacin IV during these periods were reviewed. The primary endpoint was IV:PO ciprofloxacin use ratio. Secondary endpoints were total number of ciprofloxacin doses, proportion of inappropriate IV ciprofloxacin doses, cost of therapy between phases, and estimated cost avoidance with the intervention. Results Two hundred ciprofloxacin IV treatment courses were evaluated (100 per phase). The IV:PO ciprofloxacin use ratio was 3.03 (Phase I) vs. 3.48 (Phase II). Total number of doses and ratio of IV to total doses across phases were similar (p = 0.2830). IV-PO ciprofloxacin conversion occurred in 27/100 (27%) of IV courses in Phase I and 23/100 (23%) in Phase II. Proportion of inappropriate ciprofloxacin IV doses decreased between Phases I and II (244/521 (47%) vs. 201/554 (36%) (p = 0.0005), respectively). Furthermore, the proportion of pharmacist-preventable inappropriate ciprofloxacin IV doses was reduced between Phases I and II (114/244 (47%) vs. 65/201 (32%) (p = 0.0026). Proportional cost avoidance associated with total inappropriate IV use was $7,172/$16,517 (43%) (in Canadian dollars) in Phase I vs. $6,012/$17,919 (34%) in Phase II (p = 0.001). Similarly, proportional cost avoidance associated with pharmacist-preventable inappropriate IV doses was reduced from $3,367/$16,517 (20%) in Phase I to $1,975/$17,919 (11%) in Phase II (p = 0.001). Conclusion While overall utilization of ciprofloxacin remained unchanged and the proportion of IV to total doses was stable during the study period, the proportion of inappropriate IV doses and its associated costs appear to have declined subsequent to implementation of a Pharmacist-managed IV-PO Dosage Form Conversion Service. Such a program may be a beneficial adjunct in facilitating appropriate and cost-effective usage of ciprofloxacin.